The prophet Jesus and the renewal of Israel : moving beyond a diversionary debate - Horsley, Richard A (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 2012)
Debate over whether or not Jesus can be best interpreted within an "apocalyptic scenario" has continued to dominate historical Jesus studies since Schweitzer and Bultmann. In this work the author shows that the apocalyptic scenario, with its supposed expectation of "the end of the world," the fiery "last judgment," and "the parousia of the Son of Man", is a modern scholarly construct that obscures the particulars of texts, society, and history. Drawing on his wide-ranging earlier scholarship, he refocuses and reformulates investigation of the historical Jesus in a thoroughly relational-contextual approach. He recognizes that the sources for the historical Jesus are not separate sayings, but rather the sustained Gospel narratives of Jesus' mission. His approach finds Jesus the popular prophet engaged in a movement of renewal, resistance, and judgment against Roman imperialism, Jerusalem rulers, and the Pharisees
The Apocalyptic Jesus: a Diversionary Debate. The apocalyptic scenario in Schweitzer and Bultmann ; The non-apocalyptic Jesus ; Reassertion of the apocalyptic Jesus ; Apocalyptic texts, but no scenario ; Tilting at the apocalyptic windmill. -- The Prophet of Renewal: Jesus in Historical Context.Toward a relational Jesus in historical context ; Renewal of Israel in opposition to imperial rule ; The gospel sources for Jesus' mission ; Jesus leading the renewal of Israel -- Against the rulers of Israel
Includes bibliographical references and index
Keywords: Jesus Christ -- Historicity